2007
DOI: 10.1029/2006gc001326
|View full text |Cite
|
Sign up to set email alerts
|

Indications of a link between seismotectonics and CH4 release from seeps off Costa Rica

Abstract: [1] Measurements of CH 4 concentrations in the bottom water during two discrete sampling periods in subsequent years above different cold seeps at the Pacific margin off Costa Rica indicate large-scale variations of CH 4 release. CH 4 is emitted from mud extrusions and a slide scar at 1000-2300 m water depth. Maximum CH 4 concentrations were found to be lower above all investigated sites in autumn 2003 than in autumn 2002 although seep sites are up to 300 km apart. Tidal and current changes were observed but f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 37 publications
1
50
1
Order By: Relevance
“…Outside of seep habitats, where the microbial benthic methane filter is either absent or in deeper sediment zones, the adaptation might require much more time, since the doubling rate of the microbes involved is on the order of a few months (Girguis et al, 2005;Nauhaus et al, 2007;Krüger et al, 2008;Meulepas et al, 2009). Mau et al (2007) observed a reduction in methane emissions in the water column above the earthquake-impacted seepage area by 50-90 % in a period of 1 year. In our experiments, the benthic microbial methane filter required only ∼ 170 d to adapt to the new flow regime.…”
Section: Response Time Of the Microbial Benthic Methane Filtermentioning
confidence: 94%
See 4 more Smart Citations
“…Outside of seep habitats, where the microbial benthic methane filter is either absent or in deeper sediment zones, the adaptation might require much more time, since the doubling rate of the microbes involved is on the order of a few months (Girguis et al, 2005;Nauhaus et al, 2007;Krüger et al, 2008;Meulepas et al, 2009). Mau et al (2007) observed a reduction in methane emissions in the water column above the earthquake-impacted seepage area by 50-90 % in a period of 1 year. In our experiments, the benthic microbial methane filter required only ∼ 170 d to adapt to the new flow regime.…”
Section: Response Time Of the Microbial Benthic Methane Filtermentioning
confidence: 94%
“…Fluids and related methane fluxes can vary both spatially and temporally as well as in origin, composition, and flow velocity. Temporal variations can be caused by gas hydrate formation and dissociation (Hesse et al, 2000;Tryon et al, 2002;Hensen et al, 2004;Minami et al, 2012) or triggered by earthquakes, which are frequent in this active subduction zone Hensen et al, 2004;Aiello, 2005;Henrys et al, 2006;Mau et al, 2007;Fischer et al, 2013).…”
Section: Geological Settingmentioning
confidence: 99%
See 3 more Smart Citations